1974
DOI: 10.2466/pr0.1974.35.1.447
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Tokens: Increasing Social Interaction in Token Economies

Abstract: Patients in token-economy programs are generally unable to reinforce each other's behavior with tokens and social interaction among patients is usually minimal. In this study, all patients on a token economy ward of a state hospital were given a daily allowance of special transferable tokens in addition to whatever other tokens they earned. Transferable tokens could be spent by any patient except the one to whom they were issued. Both the frequency of social interaction and the number of different patients int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1978
1978

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Other group programs are developed to deal with specific behavioral problems that interfere with court competency or successful readjustment within the prison environment. • One example of a specialized group program developed on the treatment wards is the transferable token system, modeled after a program developed by Abrams, Hines, Pollack, Ross, Stubbs, & Polyot (1974). This program was designed to increase the rate of social interactions among withdrawn patients of the Georgia Forensic Services Center.…”
Section: Treatmentmentioning
confidence: 99%
“…Other group programs are developed to deal with specific behavioral problems that interfere with court competency or successful readjustment within the prison environment. • One example of a specialized group program developed on the treatment wards is the transferable token system, modeled after a program developed by Abrams, Hines, Pollack, Ross, Stubbs, & Polyot (1974). This program was designed to increase the rate of social interactions among withdrawn patients of the Georgia Forensic Services Center.…”
Section: Treatmentmentioning
confidence: 99%
“…Buell, Stoddard, Harris, and Baer (1968) found that they could increase a 3-year-old girl's rate of desirable social behaviors by reinforcing her for use of playground equipment, a tactic that brought her into close proximity with other children. Finally, Abrams, Hines, Pollack, Ross, Stubbs, and Polyot (1974) increased social interaction among the patients 'This study was conducted under the supervision of Teodoro Ayllon, to whom grateful acknowledgement is made. While the procedures employed were directed by Dr. Ayllon, the authors take full responsibility for this presentation of the results.…”
Section: Georgia State Universitymentioning
confidence: 99%